ANALISIS PENGUKURAN PELAYANAN TERHADAP TINGKAT KEPUASAN MASYARAKAT PADA UNIT PELAYANAN PENDAPATAN DAN PEMBERDAYAAN ASET DAERAH (UP3AD) KABUPATEN WONOGIRI - SRIWIJIASTUTI SRIWIJIASTUTI@GAMIL.COM; TEGU SRI ROHMAT (JURNAL WIDYA GANECWARA, 2017)
The purpose of this study were: (1) to measure the level of quality of services provided by Up3ad Wonogiri District given to customers. (2) to measure the suitability of implementation and customer expectations on the level of quality of services provided by Up3ad Wonogiri District.   This research was conducted at Up3ad Wonogiri District. The population in this study were all community/user of Up3ad in Wonogiri. In this study, samples were taken by 90 community/user with convinience sampling method.   Problem statement: (1) Is the level of implementation has been in accordance with the interests and expectations of customers, so as to satisfy community/user? (2) Is the quality of services provided by Up3ad Wonogiri District already at the level of satisfying community/user?   The results of this study can be concluded that in general the average level of the suitability of each dimension no one has reached 100 percent, so there are several dimensions that need to be improved, namely tangible dimension and the dimension of empathy. Dimensions closest customer expectations consist of dimensions of responsiveness, assurance and reliability. While community/user satisfaction index (CSI) to attribute the quality of services Up3ad Wonogiri amounted to 89.69%. These results explain that the satisfaction level of overall service quality attributes assessed from customer Up3ad Wonogiri has a level of  "Very Satisfied"